2016
DOI: 10.2147/oajsm.s113020
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of functional outcomes in patients undergoing revision arthroscopic repair of massive rotator cuff tears with and without arthroscopic suprascapular nerve release

Abstract: PurposeThis study was designed to compare functional outcomes in patients undergoing revision repair of massive rotator cuff tears (retracted medial to the glenoid) with Goutallier Grade 4 atrophy and concomitant release of the suprascapular nerve to a similar group of patients with Grade 3 atrophy undergoing revision rotator cuff repair (RTCR) without nerve release. We hypothesized that patients undergoing nerve release would have more favorable functional outcomes as measured by the Modified University of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…They concluded that the patients with nerve release presented with better functional recovery and less pain at the final follow-up. 21,22 However, Gerber et al, 23 in a prospective randomized trial of a small number of patients (N ¼ 19), did not find any difference between the release and non-release groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They concluded that the patients with nerve release presented with better functional recovery and less pain at the final follow-up. 21,22 However, Gerber et al, 23 in a prospective randomized trial of a small number of patients (N ¼ 19), did not find any difference between the release and non-release groups.…”
Section: Discussionmentioning
confidence: 94%
“…Many researchers have reported significant differences comparing postoperative clinical improvements after rotator cuff repairs with versus without SSN release. 6,8,9 Zunkiewicz et al 21 and Savoie et al 22 are the only researchers who reported the results of patients undergoing revision cuff repair and compared the results in 2 groups: patients with SSN release and those without SSN release. They concluded that the patients with nerve release presented with better functional recovery and less pain at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with suprascapular neuropathy in the setting of MRCT, there is no unified treatment standard at present [ 6 , 20 , 27 , 28 ]. For the treatment of suprascapular neuropathy, Lafosse et al described the technique of arthroscopic transverse scapular ligament dissection in 2007 and nine out of ten patients had satisfactory outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suprascapular nerve (SSN) is often compressed along its course, especially at the suprascapular notch and the spinoglenoid region [ 4 , 5 ]. The mechanism of nerve injury can be roughly classified as compression or traction resulting from massive rotator cuff tears [ 6 , 7 ], space-occupying leisongs [ 8 – 11 ], anatomic variations of suprascapular ligament [ 12 ] and spinoglenoid ligament [ 9 , 13 ], distal clavicle [ 14 ] or scapular fractures [ 15 ], vascular compression [ 16 , 17 ] and dynamic compression in athletes [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported better clinical outcomes by additional decompression of the nerve. 35,39 Others reported excellent clinical outcome and reversal of a suprascapular nerve pathology by RC repair without additional decompression. 8,28 The risk of suprascapular nerve decompression, however, has never been assessed quantitatively.…”
mentioning
confidence: 99%